Nutzen und Risiken des Mammographiescreenings - Junkermann, Hans (Der Onkologe, 2017)
Background: Mammography screening is partly being questioned in public. Objective: Description of advantages and disadvantages of participation in mammography screening programs. Material and methods: Analysis of international primary literature, reviews and statements of expert panels. Results: Concerning the reduction of breast cancer mortality, the established mammography screening programs achieve or surpass the results of the randomized studies on which they were based. Disadvantages, such as overdiagnosis and false positive suspicious findings, which are inherent to any early detection program, have to be balanced against this advantage. The quantitative assessment of these advantages and disadvantages requires a high level of epidemiological expertise. The majority of qualified expert panels recommend mammography screening for the age group 50-70 years. Rejection partially results from incomplete or inadequate analysis of the studies. Conclusion: Participation in mammography screening programs can be recommended for women in the appropriate age group. Individual women should be placed in a position to be able to decide on participation on the basis of the results of the programs and own preferences as much as possible.